The story of Harriet Tubman : conductor of the underground railroad - McMullan, Kate.; Petruccio, Steven (New York : Bantam Doubleday Dell Books for Young Readers, 1991)
A biography of the former slave who became a "conductor" on the Underground Railroad and lead over 300 slaves to freedom.
"A Yearling book."
5.5
3-6.
Keywords: Tubman, Harriet, -- 1820?-1913 -- Juvenile literature; Slaves -- United States -- Biography -- Juvenile literature; African Americans -- Biography -- Juvenile literature; Underground railroad -- Juvenile literature; Slavery -- United States -- Anti-slavery movements -- Juvenile literature; Slaves; African Americans -- Biography; Underground railroad; Slaves -- United States -- Biography; African Americans -- Biography; Underground railroad